Physico-chemical changes in lettuce (Lactuta Sativa Linn) stored at room and refrigerator temperature - Ferrer, Edna R. (1979)
Leafy type lettuce, grown four weeks after planting, was stored at room temperature ranging from 83.5 to 86.0°F and refrigerator temperature ranging from 53.0 to 60.5°F for seven days. Each day, physico-chemical changes of samples from both storage temperatures were analyzed which include measurement of weight loss respiration rate, chlorophyll content, amount of reducing sugar and Vitamin C content. The weight, chlorophyll and vitamin C contents of lettuce decreased after a week storage at both temperatures. However, the rate of decrease was faster at room than at refrigerator temperature. The respiration rate was observed to increase steadily at room temperature while the reverse happened to the samples at refrigerator temperature. The reducing sugars of samples stored at refrigerator temperature increased but those at room temperature decreased steadily during the seven days of storage.